Analysis of Biogas Production From Fermentation Results of Pineapple Bark Waste as Main Raw Material - Fatkur Rhohman; Hesti Istiqlaliyah (Procedia of Engineering and Life Science, 2021)
The need for energy is currently increasing. But, dependence on fossil energy is very high. So, there needs a real effort to develop new and renewable energy sources. One of the sources that can be developed for energy is biogas. Many natural resources can be used as raw material for biogas production, such as pineapple skin waste which is widely available in Kediri. This study aims to analyze the results of biogas production from a combination of pineapple skin, cow dung, EM4, and water. This research uses a qualitative approach. The research method is experimental research. The composition ratio used was 50 kg of pineapple skin, 50 liters of water, 2 kg of cow dung, and 2 liters of EM4. The study time was 30 days. the overall biogas production yield was 0.204 kg. The biggest increase in biogas production occurred on day 17 to day 25. From the results of data processing using numerical methods, the graphical equation of biogas production is described by the equation . y represents the volume of biogas production in grams. x represents the counted days to determine the production process.